The Power of Workshop - Stephanie Nagl (Networks: An Online Journal for Teacher Research, 2020)
This action research explores the use of Readers’-Writers’ Workshop (RWW) in the secondary English classroom. RWW often requires a paradigm shift on the part of the teacher to allow for more student autonomy and limiting direct instruction time. The researcher sought to discover whether or not this model would impact the engagement level and the attitudes toward reading of high school seniors. Findings suggest RWW can be an effective tool for engaging students, as well as, helping students to develop positive attitudes with reading practices.
Keywords: Readers’ Workshop; Writers’ Workshop; secondary; English classroom; engagement